Working Memory Power Test for Children. (February 2019) - Chalmers, Kerry A.; Freeman, Emily E.
Low working memory (WM) capacity has been linked to poor academic performance and problem behavior. Availability of easy-to-administer screening tests would facilitate early detection of WM deficits. This study investigated the psychometric properties of the Working Memory Power Test for Children (WMPT) in 170 Australian schoolchildren (8½-11 years). Reliability (internal consistency) and validity of WMPT accuracy scores were examined. WMPT accuracy predicted achievement in reading, numeracy, and spelling. The results provide preliminary evidence of reliability and validity that supports interpretation of the WMPT accuracy score. With additional research, the WMPT could be valuable as an easy-to-administer screener for WM deficits.